2011
DOI: 10.1017/s1368980011002795
|View full text |Cite
|
Sign up to set email alerts
|

Beverage consumption and BMI of British schoolchildren aged 9–13 years

Abstract: Objective: Adequate fluid intake has been well documented as important for health but whether it has adverse effects on overall energy and sugar intakes remains under debate. Many dietary studies continue to refrain from reporting on beverage consumption, which the present study aimed to address. Design: A cross-sectional survey investigated self-reported measures of dietary intake and anthropometric measurements. Setting: Primary and secondary schools in south-west London, UK. Subjects: Boys and girls (n 248)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Patterns of beverage consumption varied by age. Milk consumption declined with age whereas the consumption of sweetened beverages increased, consistent with other data from France [26, 27], the UK [16], and the US [5]. Total water intakes in the UK, but not in France, varied with income.…”
Section: Discussionsupporting
confidence: 87%
“…Patterns of beverage consumption varied by age. Milk consumption declined with age whereas the consumption of sweetened beverages increased, consistent with other data from France [26, 27], the UK [16], and the US [5]. Total water intakes in the UK, but not in France, varied with income.…”
Section: Discussionsupporting
confidence: 87%
“…Sugar‐sweetened beverages are the main contributors of sugar intake in UK children, but few observational studies have examined associations between ASBs and energy and sugar in children, together having uncertain results . A clinical trial in children found that total energy and sugar intake were reduced after replacing SSBs with non‐sugary drinks for 2 years, but non‐sugary drinks comprised varying unsweetened options, including water, so definite conclusions concerning ASBs are hard to be drawn .…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence from cross-sectional studies has been mixed, many of these studies support a positive association between added sugar intakes and adiposity. 3449 …”
Section: Cvd Risk Outcomes Associated With Added Sugars Intakementioning
confidence: 99%
“…60 Other studies have found no association with weight gain or adiposity in all age groups specifically when adjusted for total energy. 34,3739,41,45,6166 A few studies have shown mixed results in which SSBs were associated with BMI increases in their sample in girls 66 or boys 39 but not both.…”
Section: Cvd Risk Outcomes Associated With Added Sugars Intakementioning
confidence: 99%